MODEL OF PLANNING FOR CHEMICAL MATERIAL REQUIREMENTS IN THE ENVIRONMENTAL LABORATORY UPTD OF THE ENVIRONMENTAL SERVICE OF BATANG HARI REGENCY - Armando, Fitra; Riski Gusti, Diah; Nizori, Addion (JPASDEV : Journal of Public Administration and Sociology of Development, 2025)
Planning of chemical needs plays an important role for testing laboratories. Unoptimal planning will resulted in inadequate procurement of chemicals. Excess procurement can cause chemicals to build up in storage and become obsolete. Meanwhile, too little procurement causes sub-optimal testing services issues. This study aims to design a chemical needs planning model that can be applied in The Environmental Laboratory of The Regional Technical Executive Unit of Batang Hari Enviromentral Service. The first step in designing the model is to identify the problem by conducting interviews. Second step is conducting a literature study. Third step is designing a model with literature modification. The fourth step is to validate with experienced experts in the field of testing laboratories. The fifth step is performing a user assessment test related to the model that has been designed. The results showed that the chemical needs planning model modified by the WHO scheme, mass balance, and safety factor was declared suitable for use by testing laboratory experts. In addition, the results of the user assessment indicate that the designed model is very good and fits the needs of the Laboratory Unit.